2010
DOI: 10.1242/jcs.072389
|View full text |Cite
|
Sign up to set email alerts
|

Facilitative glucose transporter Glut1 is actively excluded from rod outer segments

Abstract: SummaryPhotoreceptors are among the most metabolically active cells in the body, relying on both oxidative phosphorylation and glycolysis to satisfy their high energy needs. Local glycolysis is thought to be particularly crucial in supporting the function of the photoreceptor's light-sensitive outer segment compartment, which is devoid of mitochondria. Accordingly, it has been commonly accepted that the facilitative glucose transporter Glut1 responsible for glucose entry into photoreceptors is localized in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 39 publications
9
38
0
Order By: Relevance
“…It had been suggested (27) that the pentose phosphate pathway in the rod outer segment could potentially supply all the NADPH reducing equivalents necessary for the reduction of all-trans-retinal to retinol. More recent studies have shown that glucose enters through transporter Glut-1 into the inner segment (28), where it is phosphorylated to glucose-6-phosphate by hexokinases I and II (29). Glucose-6-phosphate can then be utilized through the pentose phosphate pathway to generate NADPH from NADP ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…It had been suggested (27) that the pentose phosphate pathway in the rod outer segment could potentially supply all the NADPH reducing equivalents necessary for the reduction of all-trans-retinal to retinol. More recent studies have shown that glucose enters through transporter Glut-1 into the inner segment (28), where it is phosphorylated to glucose-6-phosphate by hexokinases I and II (29). Glucose-6-phosphate can then be utilized through the pentose phosphate pathway to generate NADPH from NADP ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic pathways are labeled in purple, and the enzymes controlling critical metabolic steps are shown in blue boxes. Figure modified, with permission, from (Gospe et al, 2010; Vander Heiden et al, 2009). …”
Section: Figmentioning
confidence: 99%
“…Both rod-dominated (19 -21) and cone-dominated (22) retinas use glucose in this manner. Glucose enters PRs through the Glut-1 transporters located in the inner segment of PRs (23). There it is phosphorylated by hexokinase 2 (24) and then diffuses to other parts of the cell.…”
Section: Degeneration Of Photoreceptor Neurons (Pr)mentioning
confidence: 99%